Proceedings of the 16th Annual Meeting of the Special Interest Group on Discourse and Dialogue 2015
DOI: 10.18653/v1/w15-4607
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Redundancy within a Tutorial Dialogue System: Restating Students' Responses

Abstract: Although restating part of a student's correct response correlates with learning and various types of restatements have been incorporated into tutorial dialogue systems, this tactic has not been tested in isolation to determine if it causally contributes to learning. When we explored the effect of tutor restatements that support inference on student learning, it did not benefit all students equally. We found that students with lower incoming knowledge tend to benefit more from an increased level of these types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The results showed that students in the experimental condition learned as much as students in the control condition in less time, implying that extended interaction is not always required. Another study compared two versions of Rimac: (1) the control version that always decomposes a step to its simplest sub-steps regardless of student knowledge level, and (2) the experimental version that adaptively decides to decompose a step based on student knowledge (Jordan et al, 2016(Jordan et al, , 2018. The results showed that students who used the experimental version learned similarly to those who used the control version yet spent less time.…”
Section: Excessive Interactionmentioning
confidence: 99%
“…The results showed that students in the experimental condition learned as much as students in the control condition in less time, implying that extended interaction is not always required. Another study compared two versions of Rimac: (1) the control version that always decomposes a step to its simplest sub-steps regardless of student knowledge level, and (2) the experimental version that adaptively decides to decompose a step based on student knowledge (Jordan et al, 2016(Jordan et al, , 2018. The results showed that students who used the experimental version learned similarly to those who used the control version yet spent less time.…”
Section: Excessive Interactionmentioning
confidence: 99%
“…Each elicitation trial took on average 62 seconds, meaning a single evaluator can comfortably test a system in 30 minutes using the taxonomy version and exam size used here. This should allow evaluation well within the time frame typically required for current dialog system evaluations with human subjects such as (Jordan, Albacete, and Katz 2015;Pincus, Georgila, and Traum 2015).…”
Section: Measure Cleverbotmentioning
confidence: 99%